GAMBARAN KELENGKAPAN PENGISIAN LEMBAR PENGKAJIAN NYERI RAWAT INAP DI RUMAH SAKIT SUMBER KASIH KOTA CIREBON - Agista Putri Miranti; Sri Nurcahyati; Thia Oktiany (LPPM ITEKES Mahardika, 2021)
Incompleteness in filling out the inpatient pain assessment sheet will have an impact on the discontinuity of information and will affect the quality of health service facilities. The purpose of this study was conducted to determine the completeness of the Inpatient Pain Assessment Sheet at Sumber Kasih Hospital, Cirebon City.This type of research is quantitative descriptive. The population is the entire medical record document from January to March in 2020 with a sample of 99 medical record documents. This research instrument uses observation sheets. The results of this study indicate that there are 1 (1%) medical record documents that are completely filled and 98 (99%) incomplete medical record documents on the pain assessment sheet form. As for the conclusion in this research the completeness of the study sheet of pain in Sumber Kasih Cirebon City Hospital 1 while the incomplete study sheet of 99. And also the advice in this research is advice for hospitals should be evaluated to maintain the quality of health services improve the performance of medical record officers in the Sumber Kasih Cirebon City Hospital.